Anti-apoptotic effect of interleukin-17 in a mouse model of oxygen-induced retinopathy. (October 2019) - Li, Na; Gao, Sha; Wang, Jing; Zhu, Yanji; Shen, Xi
Abstract: Retinopathy of prematurity (ROP) is an important cause of visual loss in children born prematurely. Although the involvement of inflammation in the development of ROP is gaining increasing attention, the role of IL-17A in ROP progress remains unclear. The aim of this study was to assess the levels of IL-17A production in the mice model of oxygen-induced retinopathy (OIR) and elucidate its potential roles. Wild-type (WT) and IL-17A knockout (IL-17A −/- ) mice were exposed to 75% O2 from postnatal day 7 (P7) to P12. Age-matched controls were maintained in room air. Primary Müller cells isolated from WT or IL-17A −/- mice retina were co-cultured with 661W cells and exposed to hypoxic conditions. Western blotting and immunofluorescent staining were used to assess the expression of target protein. Apoptosis in OIR retinal sections and 661W cells was detected by TUNEL staining. Results turned out that IL-17A expression was increased and reached a peak at P22 in OIR retina and at 8 h in hypoxic-cultured Müller cells. IL-17A knockout decreased the expression of glial fibrillary acidic protein (GFAP) and mature neurotrophin-3 (NT-3) in retina of OIR mice as well as hypoxic-cultured Müller cells. The NT-3 release induced by IL-17 was prevented by an ERK-specific inhibitor. In addition, more apoptosis cells and higher levels of Bax and cleaved caspase-3 was detected in the retina tissues of IL-17A −/- OIR and the 661W cells co-cultured with IL-17A −/- Müller cells. Taken together, our findings suggest that Müller cell was the potential source of IL-17A under the hypoxic conditions. Modulation of the IL-17A/ERK/NT-3 pathway exerts anti-apoptotic effect on photoreceptor cell and may be a novel therapeutic strategy for ROP. Highlights: Retinal Müller cells were activated and secreted IL-17A under hypoxic condition. IL-17A is required in Müller cell activation under hypoxic condition. IL-17A deficiency in Müller cells exacerbates hypoxia-mediated photoreceptor cell apoptosis. IL-17A promotes mature NT-3 expression in Müller cells through ERK signaling pathway.